The Role of Modern Technologies in Managing Glycemia During Physical Activity in Patients with Type 1 Diabetes – A Literature Review - Bolesta-Okuniewska, Emilia; Borowski, Konrad; Ceryn, Julia; Kopeć, Katarzyna; Marchwińska-Pancer, Aleksandra; Michalak, Paweł; Pastuszek, Oskar; Radziwon, Maja (Quality in Sport, 2026)
Introduction. Regular physical activity is a fundamental component of therapy for type 1 diabetes (T1D), offering multidimensional benefits: from improved insulin sensitivity and weight control to reduced cardiovascular risk and enhanced psychological well-being. Despite these proven advantages, the fear of hypoglycemia remains the primary barrier preventing patients from engaging in regular exercise. Aim. The aim of this study is to provide a comprehensive review of current literature regarding the use of modern diabetes technologies - specifically Continuous Glucose Monitoring (CGM/FGM) systems and Advanced Hybrid Closed Loop (AHCL) insulin delivery systems - in the context of various forms of physical activity. Methods. A systematic search of the literature was conducted using PubMed, Google Scholar and Web of Science databases. The review prioritized clinical trials, meta-analyses, and consensus guidelines published between 2007 and 2024, with a special focus on the rapid technological advancements observed in the 2020–2024. Results. The analysis indicates that modern technologies have revolutionized the approach to exercise in T1D. CGM systems allow for proactive trend-based decision-making, while AHCL systems effectively mitigate hypoglycemia risk through automated insulin suspension. However, the efficacy of these tools is dependent on the type of exercise (aerobic vs. anaerobic) and requires specific patient education regarding "exercise modes" and nutritional strategies. Conclusion. While modern technology significantly reduces the cognitive burden of diabetes management during sports, it does not eliminate physiological challenges entirely. Future research should focus on dual-hormone systems and algorithms dedicated to high-intensity interval sports.